Immunity to SARS-CoV-2: Lessons Learned - Fergie, Jaime; Srivastava, Amit (Frontiers in Immunology, 2021)
In the year since the emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and with understanding of the etiology of the coronavirus disease 2019 (COVID-19) pandemic, it has become clear that most infected individuals achieve some form of immunity against the virus with relatively few reported reinfections. A number of vaccines have already achieved emergency use authorization based on data from large phase 3 field efficacy clinical trials. However, our knowledge about the extent and durability of this immunity, and the breadth of vaccine coverage against SARS-CoV-2 variants is still evolving. In this narrative review, we summarize the latest and rapidly developing understanding of immunity to SARS-CoV-2 infection, including what we have learned about the key antigens of SARS-CoV-2 (ie, the spike protein and its receptor-binding domain), their importance in vaccine development, the immediate immune response to SARS-CoV-2, breadth of coverage of emerging SARS-CoV-2 variants, contributions of preexisting immunity to related coronaviruses, and duration of immunity. We also discuss lessons from newer approaches, such as systems serology, that provide insights into molecular and cellular immune responses elicited and how they relate to the trajectory of infection, and potentially inform immune correlates of protection. We also briefly examine the limited research literature on immune responses in special populations, such as pregnant women and children.